Critical insights the hobbit - J.R.R. Tolkien (Massachusetts Salem Press, 2016)
J.R.R. Tolkien's novel was met with international acclaim upon its publication in 1937, given its adventurous plot, elements of high fantasy, and lovable protagonist, Bilbo Baggins. This compilation of essays closely studies the classic staple of children's literature by examining some of its themes-such as maturation and overcoming greed-exploring the world of Middle-earth, and comparing/contrasting the text with its popular sequel, The Lord of the Rings.